2014
DOI: 10.1597/12-281
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Grafted Autogenous Bone during Edgewise Treatment in Patients with Unilateral Cleft Lip/Palate or Alveolus

Abstract: Objective : To examine the changes in autogenous bone from 6 to 12 months after alveolar bone grafting (ABG) (T1) through completion of edgewise treatment (T2). Design : Retrospective longitudinal study. Setting : Multidisciplinary long-term follow-up at Kagoshima University Hospital. Patients : Forty-three patients with unilateral cleft lip and palate or alveolus. Main Outcome Measures : At T1 and T2, the bone bridge and quantity of grafted bone were evaluated using the Chelsea scale and the ABG scale. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Two-dimensional dental radiographs have been used to assess the success of ABGs for more than three decades 2 3 4 5 6 . Success was concluded based upon the measurement of bone bridges formed after bone grafting, but it has been shown that success rates can be overestimated using this methodology 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional dental radiographs have been used to assess the success of ABGs for more than three decades 2 3 4 5 6 . Success was concluded based upon the measurement of bone bridges formed after bone grafting, but it has been shown that success rates can be overestimated using this methodology 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cylinder and rectangle have a much larger range of pore sizes; however, there was no significant difference between any of the average pore heterogeneities (Figure 4(b)). Despite this, all cryogels had a fairly similar pore interconnectivity between 22 and 27,000 1/mm 3 (Figure 4(c)). Both the stacked cube and horseshoe cryogels had significantly greater pore interconnectivity than the cylinder cryogels (p < 0.05).…”
Section: Pore Analysismentioning
confidence: 98%
“…Most children with cleft lip-palate have bone missing in their alveolus (gum) and maxilla (jaw), which requires bone grafting during childhood to reunite the cleft and form a normal face. 3 As the alveolar cleft is a complex three-dimensional (3D) defect, a significant disadvantage with current treatment methods is the lack of specificity to the child. In addition, the use of bone grafts remains the gold standard for treatment which can often prove difficult as children have less donor bone availability.…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic movement of the cleft-adjacent teeth in the direction of the grafted bone can be instituted at an average of 3 months after the bone grafting, if needed. Combined interceptive bone grafting and orthodontic treatment at an early age avoid more extensive prolonged treatment later in the patient's life [5,13,19,34].…”
Section: Postgraft Orthodonticsmentioning
confidence: 99%
“…Before treatment, orthodontists should be able to explain the predicted outcome of bone grafting to patients and their parents [34].…”
mentioning
confidence: 99%